2010
DOI: 10.3892/ijo_00000738
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate inhibits the proliferation-stimulating effect of human lung cancer-associated stromal fibroblasts on lung cancer cells

Abstract: Abstract. Platelet-derived growth factor (PDGF) is a significant mediator in the proliferation of cancer-associated stromal fibroblasts (CAFs). The inhibition of CAF proliferation by blocking PDGF signaling could lead to a development of novel cancer therapy. We analyzed whether inhibiting proliferation of lung CAFs by Imatinib mesylate, which has inhibitory activity on PDGF-receptor tyrosine kinase, could suppress the proliferative activity of lung cancer cells which coexisted in the tumor tissue. First, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
(44 reference statements)
3
17
0
Order By: Relevance
“…Apart from our results, Pessina et al showed that CM from human skinderived fibroblasts treated with Paclitaxel (a chemotherapeutic drug) is a potent inhibitor of tumor cells in vitro (13). In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 53%
“…Apart from our results, Pessina et al showed that CM from human skinderived fibroblasts treated with Paclitaxel (a chemotherapeutic drug) is a potent inhibitor of tumor cells in vitro (13). In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 53%
“…If the ECM of the tumour could be modified, then drug penetration into the tumour might be facilitated. Table alludes to effects of various treatment modalities on CAFs.…”
Section: Targeting Of Caf‐related Signalling Pathwaysmentioning
confidence: 99%
“…Targeting PDGF receptors in the stroma has been found to inhibit lung cancer growth [280,281] and bone metastasis [282], and colon cancer growth and metastasis [283] in mouse models.…”
Section: Introductionmentioning
confidence: 99%